Features of the Development of the Sale of Walnuts and Walnut Products in Uzbekistan (Zien Journal of Social Sciences and Humanities, 2023)
The article discusses the best practices of foreign countries in the field of walnut growing, which is currently considered one of the main areas of horticulture, the introduction of modern intensive and innovative technologies into practice, the results of systematic increase in the yield of walnuts. As a result of the analysis, a comparative analysis was carried out based on the fact that the presence of unofficial intermediaries in the formation of prices for walnuts in the markets, mainly between producers and buyers, leads to an increase in prices for walnuts by an average of 25-30% at each stage.